Hybrid frequency between tangerine ’Cravo’ and orange ’Pêra’ crossing: analysis of morphological and RAPD markers - Oliveira, Roberto Pedroso de; Novelli, Valdenice Moreira; Machado, Marcos Antonio (Pesquisa Agropecuaria Brasileira, 2000)
The objectives of this work were to evaluate the hybrid frequency from the cross between tangerine 'Cravo' (Citrus reticulata Blanco) and sweet orange 'Pêra' (Citrus sinensis (L.) Osbeck), the use of morphological and RAPD markers for early identification of zygotic plants between parents with similar phenotype, and the morphological variability among the hybrids. Plants germinated on Petri dishes showed the higher hybrid percentage (19.4%). Hybrid plant frequency was inversely proportional to the competition level for space and nutrients among the hybrids. Accurate hybrid identification is not possible using morphological markers alone. The hybrids selected showed high morphological variability.